Sodasense: A Framework for Collecting and Managing Data from the Sensors of Mobile Devices - Βακουφτσής, Αθανάσιος (Πανεπιστήμιο Πελοποννήσου, 2023)
The aim of this thesis is to design and implement a Framework for collecting, managing and processing movement data. Initially, a brief description of the problem and the solution we offer. Then we analyze the cross-platform tools we decided to implement a test application to investigate each tool's capabilities and user experience, their advantages and disadvantages, and the reasons we rejected some of them. After, we examine the architecture of the tool in which the application was developed, its structural parts such as the manner it creates the interface, the integration of the code in two different operating systems and the tools it offers to create the application. Next, we present the features of the application which works on mobile devices that have Android and IOS operating systems. By using the application the user will be able to log into the system and share the data of their movements. The data will be stored in a central system which will process and manage them. Subsequently, we thoroughly study the development of all the functions of the application, the various screens, the user interface that each user sees and the various problems that arose and how to solve them. Later, we analyze how the application connects to the database system we created and selected after research and how the data is sent by creating a custom solution. Finally, we report the conclusions that emerged from the development of the entire framework that we created from scratch, the problems that arose during the creation of the Framework and finally the goals that we have set for the further development of the solution that we created.
Sodasense: Σύστημα για συλλογή και διαχείριση δεδομένων από τους αισθητήρες κινητών συσκευών
Μ.Δ.Ε. 98
Keywords: Sodasense; Flutter; Mobile Devices application; Data management